Contribution of Stocks, Bonds, and Mutual Funds to Indonesia's Economic Growth: An Input-Output Approach - Aiko, Hasna Zahra Rahimah; Fachriansyah, M.; Tarigan, Chairil Ihwan; Avriza, Muhammad (Bulletin of Islamic Economics, 2024)
This study analyzes the impact of conventional investment on Indonesia's economic growth through the Input-Output approach. By analyzing secondary data from the Central Bureau of Statistics and the Financial Services Authority, this study aims to identify the contribution of capital market instruments such as stocks, bonds, and mutual funds to economic growth. The analysis results show that stocks, bonds, and mutual funds significantly drive economic growth, serving as the main driver in increasing the productivity of related sectors. This research provides important insights for policymakers and investors in promoting sustainable economic development.